Autologous fat grafting to correct severe facial lipoatrophy secondary to subcutaneous panniculitis-like T-cell lymphoma: A case report with 2-year follow-up - Yiding Xiao; Yuming Chong; Yang Wang (Journal of International Medical Research)
Subcutaneous panniculitis-like T-cell lymphoma is a rare type of T-cell lymphoma that causes multiple painless subcutaneous nodules over the body. Patients with subcutaneous panniculitis-like T-cell lymphoma may develop facial lipoatrophy that causes disfigurement. We report the case of a 53-year-old female patient with subcutaneous panniculitis-like T-cell lymphoma and severe facial lipoatrophy who underwent three sessions of autologous fat grafting. During the 2-year follow-up, she regained a good facial contour after treatment.